EXPLORATION OF BIOACTIVE COMPOUNDS OF RAMBUSA (Passiflora foetida L.) ROOT EXTRACT FROM EAST KALIMANTAN COAL RECLAMATION LAND AS ANTIOXIDANT - Meray, Nishia Waya; Utami, Indah Woro; Nurazizah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
The rambusa plant (Passiflora foetida L.) is a species utilized as a cover crop due to its capacity to undergo a natural regeneration process in the context of former coal mining operations in East Kalimantan. Rambusa plants have many phytochemical properties, one of which is as an antioxidant. Nevertheless, there is currently a paucity of scientific data regarding the potential antioxidant properties of bioactive compounds in Rambusa roots utilized as cover crop plants. The objective of this study is to investigate the composition of bioactive compounds in the root extract of Rambusa plants that are cultivated on land previously utilized for coal mining in East Kalimantan, with a particular focus on their antioxidant properties. In this study, the exploration was carried out by conducting phytochemical tests using three types of solvents, namely ethanol, ethyl acetate and n-hexane and antioxidant activity tests using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method on the extracted samples. Phytochemical screening results showed the presence of alkaloid, phenolic, flavonoid, terpenoid and saponin bioactive compounds in ethanol extract; alkaloid, phenolic and steroid bioactive compounds in ethyl acetate extract. At the same time, alkaloids and steroids are contained in the n-hexane extract. The DPPH test carried out on the three extracts showed very strong antioxidant activity with IC50 values respectively for ethanol, ethyl acetate and n-hexane extracts are 6.55 ppm, 3.51 ppm and 28.71 ppm. Based on previously reported antioxidant activity data, the antioxidant activity of Rambusa (Passiflora foetida L.) roots growing on coal reclamation land is proven to have much higher activity compared to Rambusa plants growing on fertile land. Thus, the root of the Rambusa plant (Passiflora foetida L.) has enormous potential as an antioxidant and natural medicinal raw material.